"I See it Differently...": Potentials of Personalized Texts in Multi-Perspective Geography Teaching - Lütje, Astrid; Budke, Alexandra (Journal of Geography Education, 2022)
This article examines the importance of personally articulated perceptions, opinions, and judgments for multi-perspective Geography teaching. First, we highlight the theoretical potential of these personalized texts for a multi-perspective perception of the world. We then explain the methodology and the results of an analysis of Geography textbooks at lower and upper secondary level, which examines to what extent this potential is actually used. Didactically justified suggestions are given for an increased use of personalized texts in Geography textbooks.